PERTANGGUNGAN JAWABAN DALAM PERBUATAN EIGENRICHTING (Studi kasus Putusan Nomor: 263/Pid.B/2019/PN. Bgr dan Putusan Nomor 1/Pid.Sus-Anak/2020/PN Kpn) - Atika, Ginah Zulfa; Hidayat, Nur Azizah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
This study focuses on the Eigenrichting case because Eigenrichting is a case that often occurs in Indonesia, in this study discusses the different motives of crime in the Eigenrichting case contained in the Bogor court decision and the Kepanjen court decision as well as a comparison of criminal sanctions in the Eigenrichting case in the Bogor court decision and the court decision Kepanjen. This research is a normative legal research, using a case study approach. The results of this study indicate that Eigenrrichting's actions in the Bogor Court Decision Number: 263/Pid.B/2019/PN.Bgr there is an element of intent by the defendant to the victim as a result of revenge. Meanwhile, in the Kepanjen Court Decision Number 1/Pid.Sus-Child/2020/PN.Kpn there is an element of intent but in terms of protecting himself. Sanctions in the Bogor court's decision are in the form of 9 years in prison, while in the Kepanjen Court's decision the judge sentenced the defendant to a criminal coaching in the institution for 1 year.